Detection of dengue virus serotype 3 in Cajamarca, Peru: Molecular diagnosis and clinical characteristics - Aguilar-Luis, Miguel (2021)
Objective: To describe and molecularly characterize an outbreak of dengue virus (DENV) infection in Cajamarca, an Andean region in Peru. Methods: A total of 359 serum samples from patients with acute febrile illness were assessed for the presence of DENV via RT-PCR, ELISA NS1, IgM and IgG in Cajamarca, Peru from January 2017 to June 2017. The evaluation of the different diagnostic tests and their applicability was performed. Results: Dengue virus was detected in 24.7% of samples by RTPCR. Meanwhile, serological analysis detected 30.3% positive cases via ELISA NS1 antigen, 16.7% via ELISA IgG and 9.7% via ELISA IgM. Most of the cases corresponded to DENV-3 (77.5%). The use of RT-PCR performed better in primary infections (P<0.01), while detection of ELISA IgM performed better in secondary infections (P<0.01). The combination of NS1 and IgM performed better than the other assays in detecting primary (92.5%) and secondary infections (96.6%). The most frequent symptoms associated with fever were headaches, myalgias, and arthralgias across all groups. Conclusions: We report an important outbreak of dengue infection caused by DENV-3 in Cajamarca, Peru. Our findings encourage the use of NS1 antigen and IgM co-detection. These findings demonstrate an increasing expansion of DENV-3 in Peru and highlight the importance of molecular diagnosis and serotype characterization among the clinically defined dengue cases to strengthen the Peruvian epidemiological surveillance.